2023
DOI: 10.3390/antiox12091778
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Restriction Mitigates Kidney Fibrosis in an Aged and Obese Rat Model

Daniele La Russa,
Laura Barberio,
Alessandro Marrone
et al.

Abstract: Caloric restriction is an effective intervention to protract healthspan and lifespan in several animal models from yeast to primates, including humans. Caloric restriction has been found to induce cardiometabolic adaptations associated with improved health and to delay the onset and progression of kidney disease in different species, particularly in rodent models. In both aging and obesity, fibrosis is a hallmark of kidney disease, and epithelial–mesenchymal transition is a key process that leads to fibrosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(117 reference statements)
1
0
0
Order By: Relevance
“…The evaluation by Western blot analysis of the protein content of a key antioxidant enzyme, SOD1, revealed that CR enhanced the expression of SOD1. We can speculate that the latter finding may be a response signal by which CR protects prostate tissue against oxidative stress, as already reported in [79,80]. Recently, Scordino and colleagues described Hsp70/SOD1 signaling against oxidative stress damage [81].…”
Section: Discussionsupporting
confidence: 73%
“…The evaluation by Western blot analysis of the protein content of a key antioxidant enzyme, SOD1, revealed that CR enhanced the expression of SOD1. We can speculate that the latter finding may be a response signal by which CR protects prostate tissue against oxidative stress, as already reported in [79,80]. Recently, Scordino and colleagues described Hsp70/SOD1 signaling against oxidative stress damage [81].…”
Section: Discussionsupporting
confidence: 73%